No evidence for a preferential role of sleep in episodic memory abstraction - Talamini, Lucia M.; van Moorselaar, Dirk; Bakker, Richard; Bulath, Máté; Szegedi, Steffie; Sinichi, Mohammadamin; De Boer, Marieke (Frontiers in Neuroscience, 2022)
Substantial evidence suggests that sleep has a role in declarative memory consolidation. A broadly accepted notion holds that such sleep-related memory consolidation is associated with a process of abstraction. The neural underpinnings of this putative process are thought to involve a hippocampo-neocortical dialogue. Specifically, the idea is that, during sleep, the statistical contingencies across episodes are re-coded to a less hippocampus-dependent format, while at the same time losing configural information. Two previous studies from our lab, however, failed to show a preferential role of sleep in either episodic memory decontextualisation (Cox et al., 2014b) or the formation of abstract knowledge across episodic exemplars (Sweegers and Talamini, 2014). Rather these processes occurred over sleep and wake time alike. Here we present two experiments that replicate and extend these previous studies and exclude some alternative interpretations. The combined data unambiguously show that sleep has no preferential function in this respect. Rather, hippocampus-dependent memories are generalised to an equal extent across both wake and sleep time. The one point on which sleep outperforms wake is actually the preservation of episodic detail of memories stored prior to sleep.